Effect of Service Quality on Customer Trust and Its Implications on Customer Satisfaction - Dudung Juhana (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
Customer satisfaction in the pawnshop service industry requires improving service quality, and trust is mainly managed by the company well. This reason, there is a need for research on the effect of the influence of service quality on customer trust and its implications for customer satisfaction. Problem-solving proposed in this study uses a survey approach of 217 customers in a pawnshop in the Majalaya region. Data analysis used structural parametric equation modeling analysis techniques. The results of the study prove there is an influence of service quality on customer trust and its implications on customer satisfaction. The consequences of the results of the study indicate that to increase customer trust and satisfaction, and it is necessary to improve the quality of service, such as the need to consider increasing loan platpond for customers. They are expanding the ability and skills possessed by front line officers to increase customer confidence and give rewards to loyal customers.